Positioning of regional geography in the modern system of geographical sciences - Mirić, Ranko; Avdić, Boris; Bidžan-Gekić Aida; Gekić, Haris (Journal for Geography, 2020)
The main objective of this study is to provide a critical insight into the position of regional geography in modern geosciences, i.e. to examine the epistemological, methodological, practical and educational function of this synthetically oriented geographical discipline on a theoretical level. For this purpose, we have reviewed a number of readings selected from various published scientific papers and textbooks, which provide some sort of review of the modern concept of regional geography and the notion of region. The 1980s can be taken as the initial period of revitalization and redefinition of regional geography, when in addition to the traditional approach based on chorology, there was also the so-called new regional geography. The dominant concepts found in both these schools were evaluated by using the method of dialectical analysis and synthesis, on the basis of which the guidelines were proposed for future positioning of the spatial determination of the region within the geographical sciences. The general conclusion is that regional geography should not be viewed exclusively through the prism of idiographic concept, but the necessity would also be to aspire to discover the general spatial correlation patterns and regularities through various regional studies.